Caffeine use in preterm neonates: national insights into Turkish NICU practices - Unal, Sezin; Beken, Serdar; Anuk Ince, Deniz; Turan, Ozden; Korkmaz Toygar, Ayse; Ecevit, Ayse; Akcan, Abdullah Baris; Akın, Mustafa Ali; Aktas, Selma; Ciftdemir, Nukhet Aladag; Altuncu, Emel; Altunhan, Huseyin; et al. (Frontiers in Pediatrics, 2025)
ObjectiveCaffeine is a proven medication used for the prevention and treatment of apnea in premature infants, offering both short- and long-term benefits. International guidelines provide a range of recommendations regarding the preterm population eligible for caffeine prophylaxis, including the timing, dosage, and duration of treatment. Our national guidelines, published prior to the most recent updates of the international guidelines, recommend the use of caffeine citrate starting from the first day after delivery for preterm infants with a gestational age of <28 weeks. For infants up to 32 weeks, if positive pressure ventilation is required, the decision should be made on an individual basis. This study aims to describe the variability in caffeine usage across neonatal intensive care units in our country.MethodsAn online survey was sent to neonatologist who are members of the Turkish Neonatology Society to describe the variability in caffeine usage in neonatal intensive care units in our country.ResultsWe collected responses from 74 units. Prophylactic caffeine usage was observed as; GA ≤276/7: 98.6%, GA 280/7–286/7: 89.0%, GA 290/7–296/7: 75.3%, GA 300/7–316/7: 53.4%. 62.2% of units reported administering loading dose within the first two hours. The initial maintenance dose was 5 mg/kg in 64.8% of units, 10 mg/kg in 32.4% of units, and intermediate dose in 5.3% of units. 47.3% of units reported no routine dose adjustment. The postmenstrual age that caffeine treatment was stopped was found to be 34 (min-max; 32–36) weeks for infants without apnea and respiratory support, 36 (min-max; 34–52) weeks for infants without apnea but any respiratory support. The time to discharge after treatment cessation was found as; 1–4 days: 37.8%, 5–7 days: 68.9%. Among the 56 units with multiple responsible physicians, 32.1% reported intra-unit variations.ConclusionThe significant differences in caffeine usage characteristics between and within units highlight the need for clear recommendations provided by standardized guidelines.